Lower Extremity Function following Partial Calcanectomy in High-Risk Limb Salvage Patients - Noah G. Oliver; John S. Steinberg; Kelly Powers; Karen K. Evans; Paul J. Kim; Christopher E. Attinger (Journal of Diabetes Research)
Partial calcanectomy (PC) is an established limb salvage procedure for treatment of deep heel ulceration with concomitant calcaneal osteomyelitis. The purpose of this study is to determine if a relationship exists between the amount of calcaneus removed during PC and the resulting lower extremity function and limb salvage outcomes. Consecutive PC patients were retrospectively divided into two cohorts defined by the amount of calcaneus resected before wound closure: patients in cohort 1 retained = 50% of calcaneus, while patients in cohort 2 underwent resection of >50% of the calcaneus. The Lower Extremity Function Scale (LEFS) was used to assess postoperative lower extremity function. The average amount of calcaneus resected was 13% ± 9.2 (1–39%) and 74% ± 19.5 (51–100) in cohorts 1 and 2, respectively (P<0.0001). Below knee amputation was performed in 7 (28%) and 5 (29%) of subjects in cohorts 1 and 2, respectively (P=1.0). The average LEFS score was 33.9 ± 15.0 for subjects in cohort 1 and 36.2 ± 19.9 for the subjects cohort 2 (P=0.8257) which correlates to “moderate to quite a bit of difficulty.” Our study suggests that regardless of the amount of calcaneus resected, PC provides a viable treatment option for high-risk patients with calcaneal osteomyelitis.